From Trinidad to Cyberspace: Reconsidering Ernst Toch’s “Geographical Fugue” - Carmel Raz (Zeitschrift der Gesellschaft für Musiktheorie)
Ernst Toch’s “Geographical Fugue” was conceived of as a work for technological media, designed as a recording to be ‘performed’ by gramophone set to a faster speed. Perhaps uniquely in music history, this electronic work has had an almost exclusively acoustic performance history of more than eight decades. Premiered in 1930 at a Berlin-based festival dedicated to the incorporation of technology in music, a few years later the piece was transformed into a humorous showpiece spoken live by a-cappella choirs. However, these renditions represent a substantial deviation from the composer’s intention.